PENGARUH MODEL PEMBELAJARAN REALISTICMATHEMATIC EDUCATION (RME) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK PGRI 2 PALEMBANG - Tika Dwi Nopriyanti; Monika Erlina; Andinasari Andinasari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The era is increasingly sophisticated and modern so that every teacher must be innovative and creative in choosing a learning model to improve students 'abilities, especially students' mathematical problem solving abilities so that. This research is an experimental study with Posttest-Only Control Design. The study was conducted in class X TO 4 and X TO 6 SMK PGRI 2 Palembang in the academic year 2018-2019 with a test at the end of the meeting as a tool to measure students' mathematical problem solving abilities with results of tcount 2,693 thus it can be concluded that there was a significant effect of Realistic Matematic learning model Education (RME) on mathematical problem solving skills of students of SMK PGRI 2 Palembang.